Effect of business subsidies on labour demand: overall evaluation with regional extensions - Aki Kangasharju; Takis Venetoklis (European Regional Science Association (ERSA), 2002)
This paper investigates the effects of business subsidies on the employment of firms, and explores possible regional differences in the effects. Employment of firms is annually followed between 1995-1998. We find that employment subsidies increase firms' own employment payroll on average by 5.0 - 5.5 per cent. At the average values however, the marginal effect of subsidies is 10 percent, i.e. one Euro higher subsidy increases subsidies by 10 cents. This suggests that the proportion of subsidies of the average-waged employee is as high as 91 per cent. In contrast, we do not find positive or negative effect of Investment and operation subsidies or R&D subsidies on employment of firms. Finally, regional results show that the subsidy effects have been slightly stronger in central areas of Finland than in countryside, suggesting that employment subsidies have contributed to divergence of regional economies in Finland.
Keywords: 330